The Impact of the Combination Therapy of Listening to the Holy Quran and Progressive Muscle Relaxation on Blood Pressure Reduction in Women of Reproductive Age with Hypertension: A Randomized Controlled Trial Study - Ningsih, Erna; Islamiyati, Islamiyati; Riyanto, Riyanto; Gumelar, Rizki (Jurnal Kesehatan Metro Sai Wawai, 2024)
Introduction: Hypertension is a global public health problem, including Indonesia as a silent killer. Nonpharmacological (complementary) therapies are experiencing an increasing trend to be given along with pharmacological therapy requires evaluation as a blood pressure lowering for evidence-based practice. Objective: To evaluate the effect of combined therapy of listening to the Holy Quran and progressive muscle relaxation (PMR) on lowering blood pressure in women of reproductive age with hypertension. Methods: The research design used a quasi-experimental study with a pretest-posttest control group design approach. Women of reproductive age with mild and moderate hypertension in the experimental and control groups, a total of 21 participants each, were carried out at the Community Health Center in Metro City, Indonesia. Participants were given audio or listening to the Holy Quran and RPO as an experimental group and standard hypertension drug therapy in the control group. Mann-Witney test to prove the hypothesis with a significant level < 0.05 was chosen as statistical analysis. Results: This study found that women of reproductive age who were given a combination therapy of listening to the Holy Quran and PMR affected lowering their blood pressure (p-value 0,001). Participant, after being given the treatment, experienced a decrease in systolic blood pressure of 15,71 mmHg (CI 95%: 13,77-17,66) and diastolic 10,71 mmHg (CI 95%: 9,41-12,02). Conclusion: Nonpharmacological therapy (complementary) of listening to the Holy Quran audio and PMR given simultaneously can reduce blood pressure in women of reproductive age with hypertension. Therefore, this complementary therapy can be used as a companion therapy along with conventional therapy for community health services.Latar Belakang: Hipertensi menjadi masalah kesehatan masyarakat global, termasuk Indonesia sebagai silent killer. Terapi nonfarmakologi (komplementer) mengalami trend peningkatan untuk diberikan bersamaan dengan terapi farmakologi memerlukan evaluasi sebagai penurun tekanan darah untuk evidence base practice. Tujuan: Untuk mengevaluasi efek terapi kombinasi mendengarkan Al-Qur’an dan relaksasi otot progresif (ROP) terhadap penurunan tekanan darah pada wanita usia subur dengan hipertensi. Metode: Rancangan penelitian menggunakan studi quasi eksperimen pendekatan pretest posttest control group design. Wanita usia subur dengan hipertensi ringan dan sedang pada kelompok eksperimen dan kontrol masing-masing total 21 sebagai Partisipan yang dilaksanakan di Pusat Kesehatan Masyarakat di kota Metro, Indonesia. Partisipan diberikan terapi audio mendengarkan al-quran dan ROP sebagai kelompok eksperimen dan pemberian terapi obat standar hipertensi pada kelompok control. Uji mann-witney untuk membuktikan hipotesis dengan tingkat signifikan < 0,05 dipilih sebagai analisis statistic. Hasil: Studi ini menemukan bahwa ada pengaruh wanita usia subur yang diberikan terapi kombinasi mendengarkan al-quran dan ROP terhadap penurunan tekanan darah (p-value 0,001). Partisapan setelah diberikan perlakuan mengalami penurunan tekanan darah sistolik 15,71 mmHg (CI 95%: 13,77-17,66) dan diastolic 10,71 mmHg (CI 95%: 9,41-12,02). Simpulan: Terapi nonfarmakologi (komplementer) mendengarkan Al-Qur’an dan relaksasi otot progresif yang diberikan bersamaan mampu memberikan efek penurunan tekanan darah pada wanita usia subur dengan hipertensi. Oleh karena itu, terapi komplementer ini dapat dijadikan terapi pendamping bersamaan dengan terapi konvensional untuk pelayanan kesehatan komunitas.